Apakah Tanggung Jawab Sosial Perusahaan Memediasi Pengaruh Karakteristik CEO terhadap Tingkat Penghindaran Pajak? - Pranoto, Sulaksono Suryo; Narsa, I Made (E-Jurnal Akuntansi, 2021)
The purpose of this study is to test empirically whether CSR can mediate the effect of CEO characteristics on the level of tax avoidance. The variables studied were political experience; academy affiliation; educational background abroad; gender. The sample in this study were manufacturing companies listed on IDX in 2017-2018, there are 179 companies listed in manufacturing companies. This study uses purposive sampling on manufacturing companies that meet certain criteria. The analysis technique used is path analysis. This study produces findings that CSR analysis can mediate the effect of political experience on the level of tax avoidance; CSR can mediate the effect of academic affiliation on the level of tax avoidance; CSR can mediate the influence of educational backgrounds abroad on the level of tax avoidance; CSR can mediate the effect of gender on the level of tax avoidance. Keywords:   Corporate Social Responsibility; Political Experience; Academy Affiliates; Overseas Educational Background; Gender; Tax Avoidance Rates.